(untitled) (World Bulletin of Public Health, 2024)
to study the value of the CSP-DM-HypoGl (Comprehensive Symptom Profile-Diabetes Mellitus Hypoglycemia Module) questionnaire in patients with type 1 and type 2 diabetes mellitus according to negotiability data